T232K/K238Q Aerolysin Nanopore for Mapping Adjacent Phosphorylation Sites of a Single Tau Peptide. Issue 11 (5th May 2020) - Li, Shuang; Wu, Xue‐Yuan; Li, Meng‐Yin; Liu, Shao‐Chuang; Ying, Yi‐Lun; Long, Yi‐Tao
Abstract: Tau phosphorylation shows direct clinical importance as the hyperphosphorylation and aggregation of tau exists in a range of tauopathies. However, it is still challenging to study tau phosphorylation owing to its multiple and adjacent phosphorylation sites in the tau sequence. To address this challenge, here, a designed T232K/K238Q mutant aerolysin nanopore is introduced which synergistically incorporates the enhanced electrostatic interaction at T232K site and the high repelling barrier at K238Q site. The distinct current blockages produced by a T232K/K238Q aerolysin sensor achieve nearly 100% identification accuracy for the characteristic distribution of unphosphorylated tau peptide, pS262‐, pT263‐tau peptide, and pS262/pT263‐tau peptide. The excellent sensing ability of the T232K/K238Q nanopore originates from the extremely slow translocation speed which prolongs the duration up to tens or hundreds milliseconds for a nine‐amino‐acid peptide. It is envisioned that the design ideas of the T232K/K238Q aerolysin nanopore can be further applied to analyze other protein/peptide post‐translational modification as it provides the exquisite sensitivity for identifying the modification of single amino acids. Abstract : A T232K/K238Q mutant aerolysin nanopore is designed to achieve the direct detection of tau peptide, pS262‐, pT263‐ tau peptide and pS262/T263‐tau peptide in the mixture with a nearly 100% identification accuracy for their characteristic peaks. This work provides very promising design ideas of mutant nanopores for realizing protein sequencing in an encouraging way.